ANALISIS PERBEDAAN KADAR ALBUMIN SEBELUM DAN SESUDAH HEMODIALISA PADA PASIEN GAGAL GINJAL KRONIK DI LABORATORIUM DI RUMAH SAKIT SANTA ELISABETH - Fitri Agnes Simatupang; Anak Agung Ayu Eka Cahyani; Moh Fairuz Abadi (PT. GIAT KONSELING NUSANTARA, 2026)
Chronic kidney failure (CKF) is a progressive decline in kidney function so that it connot maintain hemostasis in the body, in order to maintain hemostasis in the body, hemodialysis is performed on patients with kidney failure, to replce kidney function. Albumin examination is serum or plasma taken from venous blood. The purpose of this study was to analyze albumin levels in patients with chronic kidney failure before and after hemodialysis at Santa Elisabe Hospital Medan. This research method uses non-probability sampling quota. The population in this study was 176 patients with a sample size of 64 respondents. The results of the study showed that albumin levels before hemodialysis in patients with chronic kidney failure had an average of 2.8484 g/dL. Albumin levels after hemodialysis had an average of 3.1719 g/dL, the results of the statistical analysis obtained a p-value of 0.000. this shows that the p-value<0.005, which means that H0 is rejected and H1 is accepted, so it can be concluded that there is a difference in albumin levels before and after hemodialysis in patients with kidney failure.